Nutrition assessment clinical and research applications - Munoz, Nancy; Bernstein, Melissa (Jones & Barlett Learning, 2019)
Written for the graduate-level nutrition course, Nutrition Assessment: Clinical and Research Applications explores the purpose, methods, and scientific basis for nutritional assessment in community, clinical, and individual nutrition settings. It provides students with the basic knowledge and skills to identify nutrition problems, develop research questions and study hypotheses, and plan nutrition interventions and treatments.